What Should a Clever Moose Eat? Natural History, Ecology, and The North Woods - Pastor, John.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2016)
John Pastor explores the natural history of the North Woods, an immense and complex forest that stretches from the western shore of Lake Superior to the far coast of Newfoundland. From the geological history of the region to the shapes of leaves and the relationship between aspens, caterpillars, and predators, Pastor delves into a fascinating range of topics as diverse as the North Woods themselves. Through his meticulous observations of the natural world, scientists and nonscientists alike learn to ask natural history questions and form their own theories, gaining a greater understanding of and love for the North Woods$1 (Band other natural places precious to them.s
1. Setting the Stage -- 2. The Emergence of the North Woods -- 3. The Birth and Death of a Beaver Pond -- 4. David Thompson$1 (Bs Canoe -- 5. How Long Should a Leaf Live? -- 6. The Shapes of Leaves -- 7. The Shapes of Crowns -- 8. How Should Leaves Die? -- 9. Foraging in the Beaver$1 (Bs Pantry -- 10. Mouse Wars, Fungi, and Spruce -- 11. What Should a Clever Moose Eat? -- 12. Tent Caterpillars, Aspens, and the Regulation of Ecosystems -- 13. The Diversity of Warblers and the Control of Spruce Budworm -- 14. The Dance of Hare and Lynx -- 15. Skunk Cabbages, Blowflies, and the Smells of Spring -- 16. When Should Flowers Bloom and Fruits Ripen? -- 17. Everybody$1 (Bs Favorite Berries -- 18. Coevolution of Crossbills and Conifer Cones -- 19. Does Fire Destroy or Maintain the North Woods? -- 20. The Legacies of a Fire -- 21. The Correlated Evolution of Serotiny, Flammability, and Fire.s
Keywords: Life sciences; Ecology; Nature conservation; Life Sciences; Ecology; Nature Conservation; Electronic books